Bitcoin transactions as a graph. Issue 3 (8th September 2022) - Di, Zhensheng; Wang, Guan; Jia, Lili; Chen, Zhuoyi
Abstract: Nowadays, blockchain is an upcoming area for researchers from different research fields. Bitcoin, as the first successful cryptocurrency, has accumulated numerous data after its existence. Here, the Bitcoin transaction graph from a graph theory perspective is investigated with more available data given now. This paper mainly focuses on the transaction graph and provides researchers with both practical and theoretical sides of the data. Several existent measurements and some newer ones are first computed and analysed. These measurements help to interpret the transaction graph more extensively. A new modified Buckley–Osthus random graph model is proposed, and a simulation of the Chung–Lu model is attempted to represent the Bitcoin transaction network. Some suggestions are given to improve the modified Buckley–Osthus model and point out the pros and cons of these random graph models. Moreover, the experiments show that scale‐free networks are fundamentally not a good model for Bitcoin transaction networks considering all the data, but the mechanics of preferential attachment is crucial. How to proceed with Bitcoin transaction graph theory from both theoretical and experimental perspectives for future studies is also discussed and analysed.